Susceptibility to Undue Influence: The Role of the Medical Expert in Estate Litigation. (January 2022) - Herrmann, Nathan; Whaley, Kimberly A.; Herbert, Deidre J.; Shulman, Kenneth I.
Objectives: Medical experts are increasingly asked to assist the courts with Will challenges based on the determination of testamentary capacity and potential undue influence. Unlike testamentary capacity, the determination of undue influence has been relatively neglected in the medical literature. We aim to improve the understanding of the medical expert role in providing the courts with an opinion on susceptibility to undue influence in estate litigation. Method: Medical experts with experience in the assessment of testamentary capacity and susceptibility to undue influence collaborated with experienced estate litigators. The medical literature on undue influence was reviewed and integrated. The lawyers provided a historical background and a legal perspective on undue influence in estate litigation and the medical experts provided a clinical perspective on the determination of susceptibility to undue influence. Together, they provided recommendations for how the medical expert could best assist the court. Results: Susceptibility to undue influence is frequently used in estate litigation to challenge the validity of Wills and is defined as subversion of the testator's free will by an influencer, resulting in changes to the distribution of the estate. While a determination of undue influence includes the documentation of indicia or suspicious circumstances under which the Will was drafted and executed, medical experts should focus primarily on the susceptibility of the testator to undue influence. This susceptibility should be based on a consideration of cognitive function, psychiatric symptoms, physical and behavioural function, with evidence derived from the medical documentation, the medical examination, and the history. Conclusions: The determination of undue influence is a legal one, but medical experts can help the court achieve the most informed legal decision by providing relevant information on clinical issues that may impact the testator's susceptibility to undue influence.